2017
DOI: 10.1515/acve-2017-0026
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Thyroid Hormones Levels and Metabolism in Dairy Cows around Calving

Abstract: The hormonal activity of the thyroid gland has an important role in ruminants for the modulation of metabolic variables. In this study changes in thyroid hormones and biochemical parameters in dairy cows around calving were evaluated and the critical thyroid hormones thresholds for predicting the risk of ketosis were estimated. Blood samples were collected from 82 dairy cows at 5±3 days pre-partum and 5±3 days postpartum. Serum values of triiodothyronine (T3), thyroxine (T4), thyroid-stimulating hormone (TSH),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…MSTN has critical roles in many aspects of metabolism such as glucose and lipid metabolism [ 8 , 9 ]. Hormone levels in vivo are key to glucose metabolism, such as insulin and thyroid hormones [ 10 , 11 , 12 ]. MSTN inactivation attenuates skeletal muscle insulin resistance and regulates glucose metabolism [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…MSTN has critical roles in many aspects of metabolism such as glucose and lipid metabolism [ 8 , 9 ]. Hormone levels in vivo are key to glucose metabolism, such as insulin and thyroid hormones [ 10 , 11 , 12 ]. MSTN inactivation attenuates skeletal muscle insulin resistance and regulates glucose metabolism [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In ruminants, Fiore et al (2017) reported that thyroid hormones (T3 and T4) contributed in growth metabolism, heart contraction, cholesterol and protein synthesis, nutrients metabolism, an increased basal metabolic rate and the availability of glucose. Partial replacement of SM in the present study leads to increased thyroid hormones compared to the control group, which may be responsible for higher body weight gain through increasing basal metabolic rate.…”
Section: Discussionmentioning
confidence: 99%
“…The estimation of various hematobiochemical parameters assists in comprehending the association of blood characteristics to the habitation and adaptability of animals to the environment. Variations in blood parameters depends on the species, sex, age and nutritional and physical condition of animals (Arfuso et al, 2016;Fiore et al, 2017;Fiore et al, 2018). The investigation of blood parameters in animals represents a crucial tool in the advancement of management conditions, especially concerning the detection of healthy versus infected or stressed animals (Carcangiu et al, 2018;Arfuso et al, 2023;Perillo et al, 2021;Arfuso et al, 2022).…”
Section: Effect Of Cold Stress On Health Statusmentioning
confidence: 99%